Sikap pelajar suku kaum Suluk dan hubungannya dengan motivasi terhadap pembelajaran Bahasa Melayu sebagai bahasa kedua sekolah rendah - Jaidah, Adris (2010)
The aim of this case study is to determine the attitude and motivation of Suluk students towards the learning of the Malay Language (ML) as a second language of primary schools. It is also looking into the differences in attitude and motivation between the two genders of Suluk student learning of the Malay Language (ML) as a second language. This study uses Gardner Socio educational model (1985) as a basis of its conceptual framework. The instrument data is collected based on Chitra's study (2003) which is adopted from Setsuko Mori study (www.tuj.acjp/tesol/press/paper0014/ mori.htm). The data is distributed randomly to 100 respondents of primary four Suluk students. The respondents study in the town area A and B schools grade and one B grade rural area school. The data is analyzed using SPSS windows version 12.0 software. Statistics is analyzed using descriptive inferential, score min, standard deviation and percentage. Statistics independent-t test is analyzed at significant level of P<.O5 and Pearson Correlation at P<.01 (2-tails). Attitude Is studied from the aspects of the attitude towards the speaker of the Malay Language (ML) and integrative attitudes. Meanwhile, motivation is studied based on the aspects of attitude towards the learning of Malay Language (ML) as a second language and the desire to learn the language. The result of the study indicates the existence of significant differences between the attitudes and motivation of two genders towards the learning of (ML). As a conclusion, the result of the study shows the positive attitudes with high min towards the learning (ML). And there is significant differences in motivation between the two genders of Suluk students towards the learning of the (ML) as a second language in the primary schools